2008
DOI: 10.1111/j.1442-9071.2008.01682.x
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy of prematurity: postmenstrual age at threshold in a transitional economy is similar to that in developed countries

Abstract: Despite the relative maturity of the gestation of these infants compared with infants in developed countries who develop severe retinopathy of prematurity, the timing of treatment for threshold disease appears to be related to postmenstrual age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 7 publications
0
9
1
Order By: Relevance
“…At group 2, two patients needed laser twice and also a scleral buckle procedure and one patient needed an antiVEGF intravitreous injection of bevacizumab (Avastin ® ) in order to stop ROP progression. Comparing our data regarding the PCA at treatment for threshold ROP with the recent article published from Vietnam, as previous referenced, we observed that the PCA at treatment for inborn and for referred patients in that study were similar at 36.2 ± 2.3 weeks and 36.3 ± 2.2 weeks, respectively, while in our study the PCA for inborn was 37 weeks and the PCA for referred patients was 39 weeks, two weeks later, despite the lower BW and GA found in our patients (15) . It is well known, from the results of the Cryo-ROP, that ROP, prethreshold and threshold disease, usually occurs at completed 36 and 37 weeks of PCA, respectively.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…At group 2, two patients needed laser twice and also a scleral buckle procedure and one patient needed an antiVEGF intravitreous injection of bevacizumab (Avastin ® ) in order to stop ROP progression. Comparing our data regarding the PCA at treatment for threshold ROP with the recent article published from Vietnam, as previous referenced, we observed that the PCA at treatment for inborn and for referred patients in that study were similar at 36.2 ± 2.3 weeks and 36.3 ± 2.2 weeks, respectively, while in our study the PCA for inborn was 37 weeks and the PCA for referred patients was 39 weeks, two weeks later, despite the lower BW and GA found in our patients (15) . It is well known, from the results of the Cryo-ROP, that ROP, prethreshold and threshold disease, usually occurs at completed 36 and 37 weeks of PCA, respectively.…”
Section: Discussioncontrasting
confidence: 44%
“…Mean BW and GA for the inborn at HCPA treated for ROP in our study were 918 ± 232 g and 28 ± 2.0 weeks, respectively. These data show a lower BW and GA cohort of treated patients when compared to a similar data (1,369 ± 184 g and 30 ± 1.8 weeks) from a recent published article from Hanoi, Vietnam, a country in transitional economy, like Brazil (15) . Lower GA and BW have been implicated in the occurrence of ROP in most studies and both are considered the most important risk factors for severe ROP that require treatment in different populations and in different countries (16,17) .…”
Section: Discussionmentioning
confidence: 67%
“…Carden et al 22 reported that 58 infants referred to the National Hospital of Paediatrics in Hanoi, Vietnam with ROP had birth weights ranging from 800–1900 g and gestational ages ranging from 28–35 weeks. Gu et al 23 reported birth weights of infants with ROP in China ranging from 1501–2000 g. Risk factors reported to cause ROP in more mature neonates are septicaemia and poorly controlled oxygen therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Oxygen management inadequacies in middle-income country NICUs lead to larger infants being at risk than in high-income countries. [3][4][5] In SA, an estimated 16 000 infants are at risk of ROP and require screening each year. [2,6] In 1995, ROP accounted for 10.6% of cases of blindness in schools for the blind.…”
mentioning
confidence: 99%